Nurturing transformative local structures of multisectoral collaboration for primary health care: qualitative insights from select states in India - Shalini Singh; Emily Miller; Svea Closser (BMC, 2024)
Abstract Background Multisectoral collaboration is essential for advancing primary health care (PHC). In low- and middle-income countries (LMICs), limited institutional capacities, governance issues, and inadequate stakeholder engagement impede multisectoral collaboration. India faces similar challenges, especially at the meso-level (districts and subdistricts). Owing to its dependence on context, and insufficient evidence, understanding "How" to improve multisectoral collaboration remains challenging. This study aims to elicit specific recommendations to strengthen meso-level stewardship in India for multisectoral collaboration. The findings from this study may offer lessons for other LMICs. Methods Using purposive, maximum variation sampling, the study team conducted semi-structured interviews with 20 diverse participants, including policymakers, implementers, development agency representatives, and academics experienced in multisectoral initiatives. The interviews delved into participants' experiences, the current situation, enablers, and recommendations for enhancing stakeholder engagement and capacities at the meso-level for multisectoral collaboration. Results Context and power are critical elements to consider in fostering effective collaboration. Multisectoral collaboration was particularly successful in three distinct governance contexts: the social-democratic context as in Kerala, the social governance context in Chhattisgarh, and the public health governance context in Tamil Nadu. Adequate health system input and timely guidance instil confidence among local implementers to collaborate. While power plays a role through local leadership's influence in setting agendas, convening stakeholders, and ensuring accountability. To nurture transformative local leaders for collaboration, holistic, equity-driven, community-informed approaches are essential. The study participants proposed several concrete steps: at the state level, establish "central management units" for supervising local implementers and ensuring bottom-up feedback; at the district level, rationalise committees and assign deliverables to stakeholders; and at the block level, expand convergence structures and involve local self-governments. Development partners can support data-driven priority setting, but local implementers with contextual familiarity should develop decentralised plans collaboratively, articulating rationales, activities, and resources. Finally, innovative training programs are required at all levels, fostering humility, motivation, equity awareness, leadership, problem- solving, and data use proficiency. Conclusion This study offers multiple solutions to enhance local implementers' engagement in multisectoral efforts, advocating for the development, piloting, and evaluation of innovative approaches such as the block convergence model, locally-led collaboration efforts, and novel training methods for local implementers.